K0S and Λ production in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Klein, Jochen; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; et al. (Physical review letters, 2013)
The ALICE measurement of K0S and Λ production at midrapidity in Pb-Pb collisions at √sNN=2.76 TeV is presented. The transverse momentum (pT) spectra are shown for several collision centrality intervals and in the pT range from 0.4 GeV/c (0.6 GeV/c for Λ) to 12 GeV/c. The pT dependence of the Λ/K0S ratios exhibits maxima in the vicinity of 3 GeV/c, and the positions of the maxima shift towards higher pT with increasing collision centrality. The magnitude of these maxima increases by almost a factor of three between most peripheral and most central Pb-Pb collisions. This baryon excess at intermediate pT is not observed in pp interactions at √s=0.9 TeV and at √s=7 TeV. Qualitatively, the baryon enhancement in heavy-ion collisions is expected from radial flow. However, the measured pT spectra above 2 GeV/c progressively decouple from hydrodynamical-model calculations. For higher values of pT, models that incorporate the influence of the medium on the fragmentation and hadronization processes describe qualitatively the pT dependence of the Λ/K0S ratio.